A Distance-Aware Safety-Related Message Broadcasting Algorithm for Vehicular Networks. (24th February 2014) - Li, Xiaohuan; Hu, Bin-jie; Chen, Hongbin; Ye, Jin
A new distance-aware broadcasting algorithm was proposed to enhance the propagation distance in the latency time of safety-related message broadcasting. The IEEE 802.11p standard states that if the medium is detected as idle, a station would defer its transmission within a backoff time to avoid collisions with other stations. The backoff times follow uniform distribution over [0, CW ]. In this way, fairness among all the stations can be guaranteed. However, propagation distance was ignored and in safety-related message broadcasting fairness is not the most important issue. In the proposed algorithm, the lengths of backoff times are generated from a nonuniform distribution. They are related with the distances between the source station and its forwarding stations. The farthest forwarding station has the highest probability to forward messages. Performance of the proposed algorithm is analyzed by using a 2D Markov chain. Analytical and simulation results demonstrate that the proposed algorithm can enhance the performance of safety-related message broadcasting in terms of propagation distance, which is reflected by the successful transmission probability. The proposed algorithm does not need additional waiting time, RTS/CTS, and ACK, therefore having better compatibility with the IEEE 802.11p standard than earlier distance-aware algorithms.